Spectral analysis of two frequency response of the 1D model in interaction with the function of the transfer of "response-excitation" - Miličić Ilija M.; Kekanović Milan; Aladžić Viktorija (Zbornik Radova Građevinskog Fakulteta, 2019)
In this paper, an excitation with two different frequencies of displacement amplitudes outside the resonant region is imposed on a 1D dynamic model with resistance of the substrate. Applying FFT algorithms with MathCAD applications, are treated displacement amplitudes in the frequency and time domains respect the mapping suggested by the transfer function (I.M. Miličić, 2015). Conducted computer simulations confirmed that the harmonic response of a 1D dynamic model system can be successfully modeled based on the demonstrated equivalent solution.